The management and cost of laboratory waste associated with the conduct of research : report of a workshop (National Academy Press, 1994)
On February 10 and 11, 1994, the Government-University-Industry Research Roundtable (GUIRR) hosted a workshop on the management and cost of laboratory waste associated with the conduct of research. The goal was to identify what, if any, role the Roundtable should play in addressing concerns that waste-handling requirements are becoming so stringent and costly that they are having adverse effects on the pace and scope of research. In particular, the participants were encouraged to identify steps that research laboratories might take to improve waste-handling methods, reduce the volume of waste, eliminate nonproductive requirements, increase awareness about the importance of proper waste management, and enhance communication among all relevant parties without compromising workplace safety and environmental protection.